A versatile reporter system to monitor virus-infected cells and its application to dengue virus and SARS-CoV-2 - Pahmeier, Felix; Neufeldt, Christopher; Cerikan, Berati; Prasad, Vibhu; Pape, Costantin; Laketa, Vibor; Ruggieri, Alessia; Bartenschlager, Ralf; Cortese, Mirko (Journal of virology, 2021)
Positive-strand RNA viruses have been the etiological agents in several major disease outbreaks over the last few decades. Examples of this include flaviviruses, such as dengue virus and Zika virus, which cause millions of yearly infections around the globe, and coronaviruses, such as SARS-CoV-2, the source of the current pandemic. The severity of outbreaks caused by these viruses stresses the importance of research aimed at determining methods to limit virus spread and to curb disease severity. Such studies require molecular tools to decipher virus-host interactions and to develop effective treatments. Here, we describe the generation and characterization of a reporter system that can be used to visualize and identify cells infected with dengue virus or SARS-CoV-2. This system is based on viral protease activity that mediates cleavage and nuclear translocation of an engineered fluorescent protein stably expressed in cells. We show the suitability of this system for live cell imaging, for visualization of single infected cells, and for screening and testing of antiviral compounds. With the integrated modular building blocks, this system is easy to manipulate and can be adapted to any virus encoding a protease, thus offering a high degree of flexibility. - IMPORTANCE Reporter systems are useful tools for fast and quantitative visualization of virus-infected cells within a host cell population. Here, we describe a reporter system that takes advantage of virus-encoded proteases expressed in infected cells to cleave an ER-anchored fluorescent protein fused to a nuclear localization sequence. Upon cleavage, the GFP moiety translocates to the nucleus, allowing for rapid detection of the infected cells. Using this system, we demonstrate reliable reporting activity for two major human pathogens from the Flaviviridae and the Coronaviridae families: dengue virus and SARS-CoV-2. We apply this reporter system to live cell imaging and use it for proof-of-concept to validate antiviral activity of a nucleoside analogue. This reporter system is not only an invaluable tool for the characterization of viral replication, but also for the discovery and development of antivirals that are urgently needed to halt the spread of these viruses.